2023
DOI: 10.1111/brv.13028
|View full text |Cite
|
Sign up to set email alerts
|

How seasonality influences the thermal biology of lizards with different thermoregulatory strategies: a meta‐analysis

Danilo Giacometti,
Alexandre V. Palaoro,
Laura C. Leal
et al.

Abstract: Ectotherms that maintain thermal balance in the face of varying climates should be able to colonise a wide range of habitats. In lizards, thermoregulation usually appears as a variety of behaviours that buffer external influences over physiology. Basking species rely on solar radiation to raise body temperatures and usually show high thermoregulatory precision. By contrast, species that do not bask are often constrained by climatic conditions in their habitats, thus having lower thermoregulatory precision. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 251 publications
1
8
0
Order By: Relevance
“…Long-lived organisms experience seasonal shifts in climate multiple times over their lives (Williams et al, 2017), and seasonality has been shown to exert a strong selection pressure over the thermal biology of ectotherms (Clusella-Trullas et al, 2011; Giacometti et al, 2023). To cope with seasonality, some species may enter dormancy during periods of low environmental temperatures (Tattersall et al, 2016) or drought (Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Long-lived organisms experience seasonal shifts in climate multiple times over their lives (Williams et al, 2017), and seasonality has been shown to exert a strong selection pressure over the thermal biology of ectotherms (Clusella-Trullas et al, 2011; Giacometti et al, 2023). To cope with seasonality, some species may enter dormancy during periods of low environmental temperatures (Tattersall et al, 2016) or drought (Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, ectotherms from seasonal habitats typically exhibit different thermoregulatory behaviours, target different T b s between seasons, and are able to sustain activity across a wide range of T b s (Gilchrist, 1995; Hadamová and Gvoždík, 2011; Sepúlveda et al, 2008). Thus, by documenting seasonal changes in thermoregulatory parameters one may gain insight into the behavioural processes that underlie T b control in ectotherms (Giacometti et al, 2023). Among vertebrate ectotherms, inquiry into the effect of seasonality over thermoregulation is taxonomically biased toward lizards (e.g., Clusella-Trullas and Chown, 2014; Giacometti et al, 2023; Huey and Pianka, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations